Design and implementation of a text mining-based tool to support scoping reviews. (3rd January 2023) - Chiarello, Filippo; Gastaldi, Luca; Martini, Antonella
Among literature reviews, scoping review is a relatively new approach that is increasingly gaining popularity since it helps researchers in defining emerging and multidisciplinary fields. While artificial intelligence for text processing can help researchers in this sense, we still lack clear procedures and tools to improve the reviewing process. Following a design science approach, in this article we propose a novel tool based on natural language processing (NLP) to support scoping review and to visualise its results. The tool (NLP4Scoping) is implemented using open-source software and is made available for reuse on GitHub. Each phase for its proper application is described focusing on the nascent literature stream on innovation management in digital ecosystems.